Studi Pemodelan Numerik Penempatan Shark Fin Vortex Generator dengan Susunan Sebaris Pada Dindong Kiri dan Kanan Bus Penumpang - Haposan Misaelman Sinaga; Wawan Aries Widodo (EduInovasi: Journal of Basic Educational Studies, 2024)
This study analyzes the impact of installing Shark Fin Vortex Generators (SFVG) in a row arrangement on the left and right sides of a passenger bus on the vehicle’s aerodynamic performance. A numerical modeling approach was used to visualize the airflow around the bus and measure key parameters such as drag coefficient (CD), lift coefficient (CL), and pressure coefficient (CP) distribution. Air velocity contour analysis shows that SFVG significantly optimizes airflow around the bus. The bus with SFVG achieved a higher airspeed of 50.23 km/h, while the bus without SFVG only reached 49.83 km/h, indicating a significant reduction in aerodynamic drag. Drag coefficient (CD) analysis shows that the bus with SFVG has a lower CD value of 0.63794782 compared to the bus without SFVG, which has an average value of around 0.70191103. Although the difference is small, it indicates that SFVG has the potential to reduce aerodynamic drag. A difference in lift coefficient (CL) values between the bus with SFVG (around 0.040190537) and the bus without SFVG (around 0.05368355) was also observed, suggesting that SFVG affects the lift force distribution on the bus. Pressure distribution analysis shows that SFVG alters the pressure distribution around the bus. Pressure contours on the bus with SFVG show concentrated pressure at the front of the bus with a peak pressure of about 213.22 Pa, whereas the bus without SFVG shows a higher peak pressure, reaching 465.17 Pa at the same location. This study also evaluates the potential of SFVG to reduce fuel consumption and the environmental impact of public transportation through reduced drag forces. The analysis results indicate that SFVG has the potential to improve energy efficiency and overall aerodynamic performance of the bus. Further research is needed to fully understand the impact of using SFVG in this context.